Application of downscalling method based on the LARS-WG weather generator toassess extreme rainfall features: a case study in the coastal plain of Gio Linh District, Quang Tri Province - Tâm, Vũ Thanh; Batelaan, Okke; Lê, Trần Thành (Vietnam Journal of Earth Sciences, 2013)
The National Climate Change and Sea Water Rise Scenarios for Vietnam (NCCASWRS) updated in 2012 has been recently published by the Ministry of Natural Resources & Environment of Vietnam, which analyzes and assesses rainfall variation in accordance with three gas emission scenarios for every province of Vietnam. However, this book as targeted at national scale provides only information and data represented large areas and regions, and therefore does not provide sufficiently detailed informations that can be used as input data for hydrological modeling to assess the impact of global climate change on water resources in the area under study. This paper shares experience of the application of the downscaling method based on the LARS-WG weather generator to assesses the rainfall variation in the Gio Linh coastal plain in correspondence with three gas emission scenarios and with simulated result of the general circulation modelGFDL-CM2.1. In this study, the time series data observed at Dong Ha Gauge is used as the site baseline data, and output from the GFDL-CM2.1 model calculated for four cells surrounding Dong Ha Gauge is averaged to represent the entire Gio Linh Costal Plain. Necessary parameters for “perturbation” principle of the downscaling method is calculated and sunsequently used in the LARS-WG weather generator to generate time series data of precipitation in accordance with the three GCC scenarios. On the basis of the generated time series data of precipitation, this study focuses on analysis and interpretation of important statistical features such as variation in time of wet/dry spell length and rainfall extreme events in corespomdence with the GCC scenarios. Research result for Gio Linh Plain is also compared with relevant information addressed in the NCCASWRS book. Also based on the analysis of these statistical features this study gives preliminary assessments on the impact of GCC on water resources in the area under study.